Perancangan Desain UI/UX Untuk Aplikasi Loyalty Point Agent Menggunakan Metode Design Thinking - Dwi Putra, I Made Paramadhika; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Since the first spread of COVID-19 in Indonesia, technological developments in Indonesia have entered the industrial era 4.0. where this causes a change in habits, especially shopping where the current online shopping phenomenon makes it easy for customers to buy goods or services via mobile or websites so it is slowly replacing the existence of conventional traders. As a result, MSME business actors in this digital era need an innovation that not only attracts new customers but can also make these new customers become regular customers so that they can increase customer retention during the Covid-19 pandemic, namely by introducing a loyalty system. Even so, the current loyalty system still has shortcomings, including a loyalty system with a card where customers cannot see the points that have been accumulated, there is no complete information about the benefits obtained, the lack of variety in loyalty, and others. Therefore, this study aims to analyze the functional requirements of the loyalty point agent app that is used to introduce the loyalty system to MSME business customers. The method used in this research is Design Thinking and the result of this research is the UI/UX design of the loyalty point agent application.